Hesperidin Increase Cytotoxic Activity of Doxorubicin on Hela Cell Line Through Cell Cycle Modulation and Apoptotis Induction - Indri Kusharyanti; Larasati Larasati; Ratna Asmah Susidarti; Edy Meiyanto (ISCC (Indonesian Journal of Cancer Chemoprevention))
Combination of chemotherapeutic agent and chemopreventive agent is being a new approach in cancer treatment. This is aimed at enhancing the effectivity and also reducing drug resistance and adverse side effect of the chemotherapeutic agent. Hesperidin, a citrus flavonoid has reported to reduce the proliferation of many cancer cells. The objectives of this study were to investigate cytotoxic activities, cell cycle modulation and apoptosis induction of hesperidin and its combination with doxorubicin on Hela cell lines. MTT [3-(4,5-dimethylthiazol-2-yl)-2.5-diphenyltetrazolium bromide] assay was used to measure the growth inhibitory effect of hesperidin and its combination with doxorubicin on Hela cells. Cell cycle profile was determined by flowcytometry and the data obtained was analyzed by using ModFit LT 3.0 program. Apoptosis assay was done using double staining method using ethidium-bromide and acridine-orange. Hesperidin inhibited cell growth with IC50 48 μM, while the IC50 of doxorubicin was 1000 nM. Combination of 500 nM doxorubicin and 6 μM hesperidin showed strongest inhibitory effect toward Hela cells. Hesperidin of 24 µM accumulated HeLa cells at G1 phase, but its combination with 500 nM Doxorubicin gave G1 and S phase accumulation at 24 h incubation. Both of Hesperidin and Doxorubicin were capable of inducing apoptosis. In accordance of the apoptotic effect, hesperidin, doxorubicin and their combination decreased the expression Bcl-2 and increased the expression of Bax. According to this result, hesperidin has a potency to be developed as co-chemotherapeutic agent for cervical cancer.